2009
DOI: 10.5551/jat.no786
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X Receptor Heterodimer Variants and Cardiovascular Risk Factors

Abstract: Nuclear receptors are transcription factors that can be activated by specific ligands. Recent progress has shown that retinoid X receptor (RXR) and its heterodimerization partners, including peroxisome proliferator-activated receptors, regulate many important genes involved in energy homeostasis and atherosclerosis, and should be promising therapeutic targets of metabolic syndrome. RXR heterodimers regulate a number of complex cellular processes, and genetic studies of RXR heterodimers have provided important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 146 publications
1
20
0
1
Order By: Relevance
“…One partner of RXR is the peroxisome proliferator-activated receptor-alpha (PPARa), which is expressed in heart and vascular cells. PPARa plays a role in controlling the myocardial fatty acid oxidation and prevents cardiac hypertrophy in animal studies [23][24][25]. Of note, cardiac hypertrophy is a major risk factor for SCD, the latter being strongly reduced at high concentrations of retinol in our study.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…One partner of RXR is the peroxisome proliferator-activated receptor-alpha (PPARa), which is expressed in heart and vascular cells. PPARa plays a role in controlling the myocardial fatty acid oxidation and prevents cardiac hypertrophy in animal studies [23][24][25]. Of note, cardiac hypertrophy is a major risk factor for SCD, the latter being strongly reduced at high concentrations of retinol in our study.…”
Section: Discussionsupporting
confidence: 48%
“…In this context, the beneficial effect of high retinol may have been mediated by PPARa. Due to inhibition of inflammatory response by repressing nuclear factor kappa B and interleukin-1 as well as reduction of vascular cell adhesions molecule-1, PPARa maintain normal endothelial function [25]. Therefore, the activation of PPARa due to retinoid-activated RXR receptor can result in cardio-protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PPAR as well as PPAR may contribute to reduce the progression of atherosclerosis 5) ; however, our results showed little involvement of PPAR in the properties of nifedipine in the SHRSP heart. Our studies also showed little effect of nifedipine on RXR expression, which may also have antiatherogenic effects 7,35) , suggesting that nifedipine may selectively increase PPAR in the SHRSP heart, although the precise mechanisms of the nifedipine-induced increase in PPAR expression and its activity need to be clarified.…”
Section: Discussionmentioning
confidence: 68%
“…One primary cellular defense against ·O2 is superoxide dismutase (SOD), and the predominant activity of SOD in the vasculature is attributed to Cu/ZnSOD, which may play an important role in preventing vascular dysfunction and atherosclerosis in hypertension 1,4) . Peroxisome proliferator-activated receptors (PPARs) heterodimerize with retinoid-X receptors (RXRs) and modulate the functions of many target genes present in the endothelium, vascular smooth muscle cells (SMCs), and heart [5][6][7] . Recent evidence indicates that PPAR and PPAR exert cardiovascular protective effects independent of their metabolic actions 5,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Three separate genes encode three RXR isoforms — RXRα (RXRA), RXRβ (RXRB), and RXRγ (RXRG) – at least one of which is present in every mammalian cell (9). These subtypes are highly conserved, with near-identical ligand binding pocket conformations (1).…”
Section: Introductionmentioning
confidence: 99%